Suriyeli ailelerin eğitim hakkı algıları : Fatih-Karagümrük örneği yüksek lisans tezi - Bayram, Rukiye (My University, 2019)
Son yıllarda Suriye’de yaşanan iç karışıklıklar ve savaş nedeniyle milyonlarca insan yerinden edilmiştir. Yerinden edilen insanlar daha çok komşu sınır ülkelere göç ederek hayatta kalma mücadelesi vermektedirler. Türkiye hem diğer ülkelere girişte transit ülke, hem de kültürel ve dini benzerliklerden dolayı Suriyelilerin tercih sebebidir. Sayıca en fazla göç alan ülke konumunda olan Türkiye kayıtlı olarak dört milyona yakın Suriyeliyi barındırmaktadır. Hukuki olarak geçici koruma statüsünde bulunan Suriyeliler ağırlıklı olarak İstanbul’da yaşamaktadır. 2011 yılından bu yana Suriyeli sığınmacı sayısının gün geçtikçe artması, iç savaşın hala devam ediyor olması ve savaşın yıkıcı etkileri göz önüne alındığında Suriyeli mültecilerin Türkiye’de kalıcı olduğu anlaşılmaktadır. Yaşanan sorunlar ve çözülmeyi bekleyen problemler Türkiye’de mültecilere yönelik yapılan göç ve uyum çalışmalarını artırmıştır. Göç eden nüfus içerisinde çocuk ve genç nüfusun oldukça fazla olması eğitim konusunu gündeme getirir. Aynı zamanda uyumun sağlanması açısından en önemli konulardan birinin eğitim olduğu yadsınamaz bir gerçektir. Bu çalışmada Fatih ilçesi Karagümrük mahallesinde yaşayan on dört Suriyeli aile ile nitel çalışma bağlamında yapılandırılmış ve yarı yapılandırılmış derinlemesine mülakat ve gözlem yöntemleri kullanılarak görüşülmüş ve Suriyeli ailelerin çocuklarının eğitim hakları algıları sosyolojik ve hukuksal olarak ele alınmıştır. Çalışmanın temel sorunsalı olan mülteci ailelerin çocuklarının eğitim hakkı algılarının oldukça düşük olduğu ortaya konulmuş ve çözüm önerileri geliştirilmeye çalışılmıştır. Bu kapsamda Suriyeli yerinden edilen ailelerle veri doyumuna ulaşana dek derinlemesine mülakatlar yapılmıştır. Mülakat yapılan aileler kartopu yöntemi ile çeşitlendirilmiştir. Suriyeli çocukların eğitime katılım istatistiklerine bakıldığında kamp içinde problem görülmeyip okullaşma oranı yüksekken kamp dışında sorun oldukça büyüktür. Bu sebeple Suriyeli ailelerin yerleşik olduğu kamp dışı bir semt olan Fatih ilçesinde bulunan Karagümrük tercih edilmiştir.

In recent years, millions of Syrians have been displaced from their country as a result of internal violence, war and disorder. In order to survive, many of them have travelled to neighboring countries. However, because Turkey is a transit country and since it also shares a cultural and religious heritage with Syria, it resultingly becomes the country of choice for a significant amount of refugees to settle in. Officially Turkey is regarded as the country hosting the largest current mumber of displaced people, with official figures of around four million Syrians residing within its borders. Syrians who have been granted only a temporary protected status mainly have chosen to reside in the capital, Istanbul. As the numbers of refugees increased day by day since 2011 following the intensifying civil war, and as the full destructive impact of the conflict became apparent, it soon became understood that the Syrian refugees in Turkey would likely be staying here permanently. As a result, there was a growing expectation that the Syrians residing in Turkey would experience mounting problems and thus this prompted an increase in the amount of national works, exercises and studies oriented towards Syrian refugees. The large number of children and youth amongst the refugee population raises the issue of appropriate education. Indeed, education has been regarded as one of the most important and pressing matters pertaining to the refugees. Pertaining to this, a qualitative study was carried out in the Karagumruk neighborhood of Fatih, Istanbul-focussing on fourteen families who were also interviewed and observed as part of the study. The study approached the perceptions of the families about the rights of their children concerning education, with the study discussing the findings at both a sociological and juridical level. The fundamental issue that the study found was the fact that the refugee families perceived that the education rights of their children were very low. Thusly, several possible solutions were proposed at the close of the study. In-depth interviews were conducted with Syrian refugee families in order to obtain a sufficiently accurate picture. The families were interviewed in a diverse fashion via the snowball sampling method. When child education statistics were analysed it became evident that their was no such problem inside the refugee camps, and in fact the numbers of children attending schools were quite high. However, the story was very different with respect to the families and children outside the camps. Indeed, in their case the problem of education has remained serious. Resultingly, Karagumruk was chosen as a place of this particular study which has been focussing on this issue.
Keywords: Çocukların Eğitim Hakları; Educational Rights of Children; Göç; Migration; Mülteci; Refugee; Social Inclusion; Suriye; Uyum Syria